KEDUDUKAN JANDA DALAM HUKUM WARIS ADAT PADA MASYARAKAT PARENTAL - Eka Susylawati (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
The field of succession law in Indonesia up to now prevails law pluralism in which Islamic succession, custom succession and western succession law (Burgerlijk Wetboek) exist in society. Among those succession laws, the custom succession one is the most dominant law in society. The custom law that has dynamic characteristics also influences to the status of widow to the legacy oh her late husband, that from time to time it changes. In parental society, in the early (before RI freedom), a widow was not a heir, then the next development, the widow inherit the legacy of her late husband although the change has not received well. The cause of the change is the awareness of society in respecting the status of the widow and also because the most Indonesian society are Islam that develops the custom succession law influenced by Islamic law.